2012
DOI: 10.4149/neo_2012_085
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for invasive pulmonary fungal infection in patients with hematological malignancies not receiving hematopoietic stem cell transplant

Abstract: We investigated the incidence, pathogens and risk factors of invasive pulmonary fungal infection (IPFI) in patients with hematological malignancies who did not receive hematopoietic stem cell transplantation (HSCT). Of the 323 patients included, 106 had IPFI with confirmed diagnosis or clinical diagnosis, 111 had pulmonary bacterial infections, and 106 did not have pulmonary infections. The risk factors for IPFI were explored through logistic univariate and multivariate analysis. The incidence of IPFI in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
3
10
0
2
Order By: Relevance
“…Patients with hematological malignancies have compromised immune function, which is further impacted by radiotherapy and chemotherapy treatments. Our study patients showed no significant differences in the risk factors for IPFI which we previously identified [6]. It is also important to note that all the hospitalized patients in this study had a similar diet and performed regular brushing with similar toothbrushes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Patients with hematological malignancies have compromised immune function, which is further impacted by radiotherapy and chemotherapy treatments. Our study patients showed no significant differences in the risk factors for IPFI which we previously identified [6]. It is also important to note that all the hospitalized patients in this study had a similar diet and performed regular brushing with similar toothbrushes.…”
Section: Discussionsupporting
confidence: 51%
“…These conditions allow fungi in the mouth to migrate to the lower respiratory tract, which results in fungal infection. We previously showed that risk factors for IPFI include number of days of hospitalization, history of IPFI, number of antibiotics used, sepsis and hypoalbuminemia [6]. Theoretically, the fungi from the lung and throat have sequence homology in IPFI patients, though this homology has not been confirmed in prior published reports.…”
mentioning
confidence: 94%
“…В ряде зарубежных исследований продемонстри-ровано, что мукормикоз развивается преимуществен-но у больных острыми лейкозами [12][13][14][15][16]. Мы также показали, что острые лейкозы были фоновыми забо-леваниями у 64 % больных.…”
Section: Discussionunclassified
“…Результаты нашего исследования, а также данные литературы свидетельствуют, что у онкогематологиче-ских больных наиболее частой клинической формой мукормикоза является поражение легких (50-81 %) [2,[11][12][13]. В то же время у детей чаще развивается риноцеребральный мукормикоз (29 % vs 8 %).…”
Section: Discussionunclassified
“…Currently, IFIs constitute a clinical issue on the rise in the ICUs both in the developing and developed world [19,20] . Predisposing factors such as patients' complicated medical or surgical status, invasive bedside procedure and wide administration of antibiotics have contributed to increased rate of IFIs, mainly IC and invasive aspergillosis (IA), in the ICU [21][22][23] . Candidemia is thus far known to be the most prevalent fungal infection afflicting ICU patients [23] .…”
Section: Problem On the Risementioning
confidence: 99%